Large Eddy Simulation of a supersonic air ejector. (5th June 2022) - Croquer, Sergio; Lamberts, Olivier; Poncet, Sébastien; Moreau, Stéphane; Bartosiewicz, Yann
Abstract: This paper presents a study on the flow topology in the mixing chamber of a supersonic ejector using Large Eddy Simulation (LES). To this end, a supersonic air ejector of squared crossed-section was modelled using a specialized finite-element code. Comparisons with experimental data showed good agreement, both in terms of the primary jet shock cell structures and wall pressure measurements (mean deviation of 12%). Results have been discussed both in terms of time averaged profiles and instantaneous structures in the mixing layer. The general flow features have been identified by means of instantaneous temperature fields and pressure profiles through the device. Results show that, under the assessed conditions, the mixing layer is laminar at first and transitions towards turbulence in the first quarter of the mixing chamber, where Λ vortices have been identified. These evolve into hairpin vortices and finally break down around half of the mixing chamber. Time-averaged velocity profiles show self-similarity in this section. In comparison with an unconfined mixing layer (Fang et al., 2018), the supersonic ejector mixing layer grows slower first but then develops at a similar rate after the transition region. A shock train occurs towards the end of the mixing chamber, which enhances mixing. Given its location, it generates a recirculation bubble in the diffuser which narrows the main flow passage and breaks the flow vertical symmetry. This pioneer study shows the enormous potential that LES offers for the optimization and detailed analysis of supersonic ejectors. Highlights: Pioneer Large Eddy Simulation of an air supersonic ejector. Turbulent structures are identified along the shear mixing layer. An asymmetric shock wave/recirculation is observed in the diffuser. Application of compound choke theory to study the choking phenomenon.